2017
DOI: 10.3390/en10111911
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Flat-Plate and U-Tube Solar Collectors Using an Al2O3 Nanofluid

Abstract: Abstract:In this study, the efficiencies of flat-plate and U-tube solar collectors were investigated experimentally when an Al 2 O 3 nanofluid was used as a working fluid and compared to those of solar collectors using water. The energy savings and CO 2 and SO 2 generated were calculated and compared to those of solar collectors using water. In addition, based on the experimental results, an economic analysis of the use of solar collectors in various countries was performed. As the concentration of the Al 2 O … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The enhancement of total collector efficiency gained from MgO-MWCNTs hybrid NF was higher by 25.1 % and 16.28 % when compared with the case of water and MgO/water NF, respectively. More investigations on the thermal performance of NFs employed for FPSCs are summarized in Table 2 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Application Of Nfs To Enhance Performance Of Fpscsmentioning
confidence: 99%
“…The enhancement of total collector efficiency gained from MgO-MWCNTs hybrid NF was higher by 25.1 % and 16.28 % when compared with the case of water and MgO/water NF, respectively. More investigations on the thermal performance of NFs employed for FPSCs are summarized in Table 2 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Application Of Nfs To Enhance Performance Of Fpscsmentioning
confidence: 99%
“…Taylor et al [18,19] investigated the effectiveness of the concentrating parabolic solar collector using Al 2 O 3 nanofluid based on Therminol VP-1 and presented a 10% higher efficiency than water. Furthermore, Kang et al [20] reported that the effectiveness of flat plate and U-tube solar collectors of Al 2 O 3 nanofluid was 14.8% and 10.7% higher than that of water, respectively. With the use of coal, CO 2 generation, and SO 2 production could reduce the solar collector efficiency, when 50 flat plate solar collectors using Al 2 O 3 nanofluid were used for one year.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the value of the heat transfer coefficient was changed according to the concentration of the nanoparticles, and the mass concentration corresponding to the optimal heat transfer improvement was 1.2%. Kang et al [24] conducted an economic analysis of flat-plate and U-tube solar collectors with nanofluid (Al 2 O 3 /water). The flat-plate and U-tube solar collectors using nanofluid with a nanoparticle size of 20 nm and a concentration of 1.0 vol% had 14.8% and 10.7% higher thermal efficiency values, respectively, compared with utilizing water as the working fluid.…”
Section: Introductionmentioning
confidence: 99%